La circulation des réformes universitaires en Afrique de l'Est. Logiques de convergences et tendances aux divergences - Olivier Provini (Les éditions de la Maison des sciences de l'Homme, 2016)
Since the end of the 1980's, East African universities have reformed their governance systems and budgetary structures at different paces. These reforms are part of a larger context of policy diffusion in the higher education sector in East Africa: a set of transnational actors contributed to the establishment of a regional learning area favoring the transfer of knowledge, instruments and good practices all over the East Africa region. Against this background of regionalized policy-making, we argue that policy configurations in the higher education sector are renegotiated at the national level and shaped by the local political context. Using the case studies of the public universities of Dar es Salaam in Tanzania and Makerere in Uganda, the aim of this paper is to shed light on the transnational policy-making process in East Africa, but also to discuss the limits of the concept of policy transfers.